IOT Application on Water Intake Pump - Siregar, Ahdiat L; Hendra Saputra; Azhar Basyir Rantawi; Istianto Budhi Raharja; Widya Enzely (LPPM Politeknik Aceh Selatan, 2025)
The water needed by the Palm Oil Mill (POM) is obtained from the river that is flowed to the mill using a pump manually by the water treatment station operator, which has the potential to cause human error. This research was conducted at POM PT. Kalimantan Sawit Abadi, Citra Borneo Indah Group on March 1 - March 31, 2024. The purpose of this research is to create a series of water intake pump automation based on the Internet of Things and analyze the impact of the pump operation and workers. From this research, IoT applications are produced for water intake pump operations that can be operated and monitored using Blynk remotely and anywhere. From the use of this IoT application, workers can be allocated to other jobs so that it is more effective than just operating a water intake pump.